Implementation of Green Accounting and ESG in Management Accounting Systems to Drive Corporate Sustainable Performance - Dyah Shinta Kusumaningtyas; Heidy Happsari; Listya Ningrum (Journal of Creative Power and Ambition (JCPA), 2026)
This study examines the implementation of green accounting and Environmental, Social, and Governance (ESG) principles in management accounting systems to drive corporate sustainable performance. The background of this study is based on the growing demand for companies to integrate sustainability into internal decision-making processes, not only through external reporting but also through planning, control, and performance evaluation mechanisms. Using a qualitative descriptive approach with a literature review design, this study analyzes recent scholarly works published from 2020 onward concerning green accounting, ESG, management accounting systems, and corporate sustainability. The findings indicate that green accounting contributes to sustainable performance by enabling companies to identify environmental costs, improve resource efficiency, reduce waste, and support environmentally responsible strategic decisions. Meanwhile, ESG integration strengthens management accounting systems by incorporating environmental, social, and governance indicators into budgeting, internal control, and managerial performance measurement, thereby enhancing accountability, risk management, and long-term value creation. The study concludes that the integration of green accounting and ESG transforms management accounting systems into strategic tools for sustainability, allowing firms to balance financial objectives with environmental responsibility, social accountability, and governance quality. Therefore, the successful implementation of green accounting and ESG is essential for improving corporate sustainable performance in an increasingly competitive and sustainability-oriented business environment.